2013
DOI: 10.5592/otmcj.2013.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Professionals’ views of material wastage on construction sites and cost overruns

Abstract: It is believed that building material wastage on construction sites account for cost overruns and any improvement in building materials management on construction sites has the potential to enhance the construction industry's performance with cost-saving benefits. The purpose of this study is to identify the most wasteful building material during construction operation. It also sets out to assess the level of material wastage with various subcontracting options, the percentage contribution of material wastage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 9 publications
0
23
0
1
Order By: Relevance
“…[18,55] Cost overruns in rectifying mistakes: cost increases over the original contract value owing to rectifications of non-conformances during design and construction. [56,57] Material loss: replacing defected products or quantities that deviate from what was stipulated in the design.…”
Section: Referencementioning
confidence: 99%
“…[18,55] Cost overruns in rectifying mistakes: cost increases over the original contract value owing to rectifications of non-conformances during design and construction. [56,57] Material loss: replacing defected products or quantities that deviate from what was stipulated in the design.…”
Section: Referencementioning
confidence: 99%
“…Karim and Marosszeky [52] indicated that waste during the construction phase was largely caused by pre-construction preparations, but there were still many other factors that caused waste in the construction process. Waste during the construction process could be generated as the result of bad coordination and control [38,43,44,48], wrong choice of construction methods [7,41], and reworks [46,50].…”
Section: Construction Methods and Planning (Copl)mentioning
confidence: 99%
“…The study by Mbote et al [45], which conducted research in Kenya, showed that complex or poor designs, inadequate security, poor work conditions, and topography were the major causes of construction waste. John and Itodo [46] showed that inefficient job control, re-work, and bad material management were the important factors contributing to high material waste. Adewuyi and Otali [47] assessed the factors causing waste from construction in Nigeria.…”
Section: Construction Materials Waste Generation Factorsmentioning
confidence: 99%
“…Modular homes can be designed to be highly insulated and very air-tight, alongside being lightweight, where the modular arrangement of a house can weigh less than 30% of a typical concrete frame (Frigione et al , 2019). According to the Building Research Establishment, an average of 13% of material wastage on site is stated in the UK construction industry (John and Itodo, 2013). Subsequently, this is reduced greatly in modular construction with all off-cuts entirely recycled in the factory.…”
Section: Analysis and Findingsmentioning
confidence: 99%